Benefit of ion imprinting technique in solid-phase extraction of heavy metals, special focus on the last decade. Issue 6 (December 2021) - El Ouardi, Youssef; Giove, Alessio; Laatikainen, Markku; Branger, Catherine; Laatikainen, Katri
Abstract: Because of its many advantages, solid phase extraction (SPE) is considered to be the best process for removing heavy metals from water. Ion-imprinted polymers (IIPs) have been broadly used in the last decade as SPE adsorbents for the retention of metals ions from aqueous solutions. This itemized review list thorough literature over the last decade from 2010 until present and highlights the main results related to adsorption studies where IIPs are used as SPE adsorbents for the selective separation of heavy metals. In the first part of this review elaboration methods, components, and major polymerization techniques to produce IIPs have been described. In the second part, synthesis parameters, adsorption performance and a descriptive analysis of SPE of heavy metals by IIPs have been provided. In this review it is underlined that there are many parameters to optimize in order to obtain the required performance of the IIPs. These parameters are mainly linked to synthesis process and one of the most important is the synthesis of new ligands to improve the selectivity with respect to the target ion. Graphical Abstract: Application of IIPs as solid-phase extraction adsorbents for the removal of heavy metals in solution. ga1 Highlights: Main techniques for the preparation of IIPs are described, with their main advantages. Classification of relevant experimental parameters in the synthesis of IIPs reported in the last decade. Special focus in the application of IIPs as SPE adsorbents for the selective separation of heavy metals from simple and complex media.